Quality management impacting operational performance at Seremban Regional Operation, Petronas / Hazle Ibrahim and Mohd Munir Ahmad - Ibrahim, Hazle; Ahmad, Mohd Munir (2016)
The purpose of this study is to state the problem, identify and analyze causes affecting operational performance at PETRONAS Seremban Regional Operation (RO). This study also aims to identify the strengths, weaknesses, opportunities and threats that contribute to the operational performance related to quality management in maintenance practices. Several quality management and business tools were used to analyze the problem experienced at Seremban RO. The tools include Root Cause Failure Analysis, Fault Three Analysis, Event and Causal diagram, Strength, Weakness, Opportunity & Threat (SWOT) analysis, TOWS matrix and decision analysis by using Quadrant Analysis for Decision Making – Effort and Impact Matrix. At the end of this study, strategies that will enhance operational performance at Seremban RO are discussed. The result indicates three elements of quality management contributed to operational performance experienced by the organization. The three elements are employee training and involvement, management involvement and support and work process. Recommended strategies include assigning a number of junior staff to senior staff for coaching, direct engagement with management and establish service level agreement with nearby regional operations. Another suggested strategy is long-term. This consists of enhancement capability training matrix through online system; establish online scorecard for management monitoring and involvement and re-engineering work process for maintenance activities. Since the management support is the driving force behind the implementation of quality practices, it can be said that management support affects operational performance outcome through employee training and employee involvement.